The Perioperative Care of the Transgender Patient. (August 2018) - Tollinche, Luis Etienne; Walters, Chasity Burrows; Radix, Asa; Long, Michael; Galante, Larissa; Goldstein, Zil Garner; Kapinos, Yvonne; Yeoh, Cindy
Abstract : An estimated 25 million people identify as transgender worldwide, approximately 1 million of whom reside in the United States. The increasing visibility and acceptance of transgender people makes it likely that they will present in general surgical settings; therefore, perioperative health care providers must develop the knowledge and skills requisite for the safe management of transgender patients in the perioperative setting. Extant guidelines, such as those published by the World Professional Association for Transgender Health and the University of California San Francisco Center of Excellence for Transgender Health, serve as critical resources to those caring for transgender patients; however, they do not address their unique perioperative needs. It is essential that anesthesia providers develop the knowledge and skills necessary for safely managing transgender patients in the perioperative setting. This review provides an overview of relevant terminology, the imperative for the provision of culturally sensitive care, and guidelines for preoperative, intraoperative, and postoperative management of the transgender patient.